2007
DOI: 10.1002/mc.20280
|View full text |Cite
|
Sign up to set email alerts
|

Retinol decreases β‐catenin protein levels in retinoic acid‐resistant colon cancer cell lines

Abstract: The beta-catenin signaling pathway is dysregulated in most cases of colon cancer resulting in an accumulation of nuclear beta-catenin and increased transcription of genes involved in tumor progression. This study examines the effect of retinol on beta-catenin protein levels in three all-trans retinoic acid (ATRA)-resistant human colon cancer cell lines: HCT-116, WiDr, and SW620. Each cell line was treated with increasing concentrations of retinol for 24 or 48 h. Retinol reduced beta-catenin protein levels and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 45 publications
1
52
0
2
Order By: Relevance
“…[25][26][27] But, most studies reported that nuclear receptors repressed β-catenin signaling in the presence of ligand or agonist. 16,17,23,24 However, our data in the first time demonstrated that RXRα overexpression directly inhibited endogenous and exogenous β-catenin transcriptional activity and expression in the absence of RXR agonist. However, the inhibition was abrogated by targeted RXRα small RNA interfering.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…[25][26][27] But, most studies reported that nuclear receptors repressed β-catenin signaling in the presence of ligand or agonist. 16,17,23,24 However, our data in the first time demonstrated that RXRα overexpression directly inhibited endogenous and exogenous β-catenin transcriptional activity and expression in the absence of RXR agonist. However, the inhibition was abrogated by targeted RXRα small RNA interfering.…”
Section: Discussionmentioning
confidence: 59%
“…21,22 Recently, several lines of evidence showed that nuclear receptors affected β-catenin/TCF/LEF-mediated gene transcription and β-catenin protein. For example, retinoid-activated RAR acts as a potent repressor of β-catenin/TCF signaling in retinoid-sensitive colorectal cancer cells, 16,17,23,24 and activation of the vitamin D receptor with its metabolite ligand, 1α,25(OH) 2 vitamin D 3 , could repress Wnt/β-catenin/TCF signaling. [25][26][27] But, most studies reported that nuclear receptors repressed β-catenin signaling in the presence of ligand or agonist.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports have indicated that retinol can alter gene transcription via different mechanisms. [34][35][36][37][38] In particular, 2 classes of nuclear receptors for retinoic acid, RAR and RXR, were implicated in the effects of retinol on in vivo. 34 These receptors form heterodimers to bind to specific retinoic-acid-response elements, and have various cell-type dependent effects on cell signaling pathways, apoptosis and cell cycle arrests.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that retinol can reduce beta-catenin protein levels, which is known to be able to increase transcription of genes involved in tumor progression. 35,36 In addition, retinol may also reduce matrix metalloproteinase mRNA, protein and activity levels. 37 The chemoprevention and therapeutic potential of retinoids was subsequently explored in some cancer types, with particular success in acute promyelocytic leukaemia.…”
Section: Discussionmentioning
confidence: 99%
“…The RXR agonist decreased both β-catenin and RXRα proteins independent of the GSK-3β/APC and p53/Siah-1 degradation pathways. Previously, we showed that retinol, which is not a RXR ligand, increases the proteosomal degradation of β-catenin via a RXR-mediated pathway, but the retinol-induced activation of the RXR pathway occurred independent of a RXR agonist (14). We also demonstrated that the RXR antagonist, PA452, and the knockdown of RXRα, using RXRα small interfering RNA, inhibited the ability of retinol to decrease total cellular β-catenin levels in both cell lines, suggesting RXRα facilitates the ability of retinol to decrease β-catenin protein levels (14).…”
Section: Introductionmentioning
confidence: 98%